Transcription Analysis of the Prolate-Headed Lactococcal Bacteriophage c2 - Lubbers, Mark W. (American Society for Microbiology, 1998)
A detailed transcription map of the prolate-headed lactococcal phage c2 has been constructed. Transcription of about one-third of the genome, encoding 22 open reading frames, began within the first 2 min of infection and produced at least 12 overlapping transcripts that persisted until lysis occurred at 30 min after initiation of infection. The remaining two-thirds of the genome, encoding 17 open reading frames, was divergently transcribed, beginning between 4 and 6 min after initiation of infection, and resulted in at least 18 overlapping transcripts that persisted until lysis. Five very strong, simultaneously active, and probably unregulated early promoters and a single positively regulated late promoter were identified. The late promoter had an extended −10 sequence, had a significant basal level of activity in the uninduced state, and was induced to high activity by a phage gene product. The complex overlapping pattern of transcripts resulted from the action of the multiple early promoters, inefficient termination of transcription, and (possibly) processing of a late precursor transcript(s). Phage proteins were not required for these processes, and the host RNA polymerase was probably used for both early and late transcription.